Integrating AI in Healthcare: Advancements in Petroleum Fraud Detection and Innovations in Herbal Medicine for Enhanced Cancer Treatment Approaches - Ali Husnain; Muhammad Umer Qayyum; Muhammad Fahad; Muhammad Ibrar (International Journal of Multidisciplinary Sciences and Arts, 2024)
Artificial intelligence (AI) is transforming a number of industries, such as healthcare, detecting petroleum fraud, and herbal medicine. AI solves difficult problems and opens up new avenues for growth. This paper examines how AI has revolutionized several sectors and identifies opportunities and synergies for the future. AI is improving administrative efficiency, tailored treatment, and diagnostics in the healthcare industry. Natural language processing and sophisticated machine learning models are enhancing the precision of diagnoses, customizing care, and streamlining hospital operations. To guarantee responsible integration, however, ethical issues and data protection issues need to be taken into account. Artificial intelligence is proving to be a vital tool in the fight against petroleum fraud, particularly in the areas of financial misreporting and fuel adulteration. Real-time monitoring systems and machine learning algorithms improve fraud detection, safeguard financial assets, and guarantee regulatory compliance. AI is helping to close the knowledge gap between current science and traditional herbal treatment. Artificial Intelligence enhances the efficacy, safety, and standardization of herbal remedies by evaluating plant components and forecasting their therapeutic effects. The significance of herbal treatments in conventional healthcare is strengthened by this integration, which also holds potential for novel treatment advancements. Prospects for the future include maintaining funding for AI research, tackling moral and legal issues, encouraging interdisciplinary cooperation, and raising public awareness. AI may be fully utilized by implementing these tactics, which will advance and enhance results in the fields of herbal medicine, fraud detection, and healthcare. All things considered, artificial intelligence (AI) is a disruptive force that can alter methods, improve efficiencies, and open up new avenues for research. These fields' futures will be shaped by its sustained development and prudent application, which will also help improve technology and healthcare more broadly.